An “Engram-Centric” Approach to Transient Global Amnesia (TGA) and Other Acute-Onset Amnesias - Andrew J. Larner (Neurology International)
The differential diagnosis of acute-onset amnesia includes transient global amnesia (TGA), transient epileptic amnesia (TEA), and functional (or psychogenic) amnesia. The most common of these, TGA, is a rare but well-described condition characterised by a self-limited episode of dense anterograde amnesia with variable retrograde amnesia. Although the clinical phenomenology of TGA is well described, its pathogenesis is not currently understood, thus preventing the development of evidence-based therapeutic recommendations. Here, TGA, TEA, and functional amnesia are considered in light of the historical engram conception of memory, now informed by recent experimental research, as disturbances in distributed ensembles of engram neurones active during memory formation and recall. This analysis affords therapeutic implications for these conditions, should interventions to reactivate latent or silent engrams become available.